Preparation and Microstructure of Acetate-based Lead-free BSZT Ferroelectric Thin Films Using Sol-gel Technique - Thi Nguyet, Pham; Minh Phuong, Nguyen Thi; Hien, Vu Thu; Ngoc Hung, Vu (VNU Journal of Science: Mathematics - Physics, 2019)
Abstract: (Ba 0.85 Sr 0.15 )(Ti 0.9 Zr 0.1 )O 3 (BSZT) lead-free ferroelectric thin films at the vicinity of the morphotropic phase boundary (MPB) were successfully deposited on Pt/Ti/SiO 2 /Si using a modified spin-coated sol-gel method. Microstructure and electrical properties of the thin film were studied. High-resolution synchrotron X–ray powder diffraction (SXRD) combined with Rietveld refinement revealed that the samples were crystallized in tetragonal perovskite structure with in-plane symmetry (c < a). Raman spectra also confirmed a tetragonal perovskite crystalline lattice structure. Polarisation studies demonstrate that BSZT films exhibit a rather high saturation polarisation of 22.25 µC.cm −2 . Leakage current behavior was obtained and possible conduction mechanism is discussed. Keywords : xBST-(1-x)BZT ferroelectric materials , thin film technology, s ol-gel.